Intratumor heterogeneity in epithelial cancer: Assessment in cell line models and circulating tumor cells - Dinutanayo, Wimba W; Keilholz, Ingeborg T; Braunholz, Diana (UI Scholars Hub, 2019)
Background: CTCs are present only in small numbers in patients' blood. This study aimed to establish a protocol for enumeration and phenotypic characterization of circulating tumor cells (CTCs) by ImageStreamX MK II (AMNIS) imaging flow cytometry and to characterize the expression of epithelial, mesenchymal, and stem cell markers in CTCs. Methods: The study used the FaDu cell line at different passages, cisplatin-resistant (FaDu CDDP-R), and irradiation-resistant (FaDu IR-R) subclones, as well as blood samples from head and neck squamous cell carcinoma (HNSCC) and colorectal cancer (CRC) patients for CTC detection (n = 5). Cells were fixed using 4% paraformaldehyde and permeabilized by incubation in 0.3% Triton X-100. The cell suspensions were stained with 1:100 EpCAM AF-488, 1:50 CD45 AF-647, 1:50 Vimentin AF-555, and 1:50 ALDH1A AF-594 antibodies. Results: There were significant differences in EpCAM expression levels between FaDu at late passage and FaDu CDDP-R subclones, as well as between FaDu at late passage compared with FaDu IR-R. Furthermore, CTCs were successfully detected in five patients' samples with various CTC subpopulations. Conclusions: Intratumor heterogeneity in CTC phenotypes existed in CRC and HNSCC. Furthermore, three main subpopulations of CTCs were detected. Our findings strongly support future phenotypic studies of CTCs.